Analisis Faktor Konfirmatori untuk Mengidentifikasi Peubah Indikator Utama dalam Pengukuran Peubah Laten - Dian Handayani; Fakhirah Maryam; Faroh Ladayya; Irsyad Hasari (LPPM Universitas Negeri Jakarta, 2023)
Research on attitudes, preferences and behavior are research that involves latent variables. Latent variables are measured by observing some indicator variables. Indicator variables that measure a latent variable are selected based on the researcher's perspective, however, it is necessary to consider the previous of related research. Indicator variables need to have theoretical meaning, be valid and reliable in measuring latent variables. Confirmatory factor analysis (CFA) is a statistical method that can be used to determine the validity of the indicator variables. In this research, CFA is used to determine the main indicator variables that characterize the reasons for choosing a study program at a university by high school graduates (or equivalent). There are 20 indicator variables chosen to represent several latent factors such as image, job prospects, interests and campus facilities. The results indicate that the latent factors of image, job prospects, interest and facilities can be respectively represented by the majority of alumni occupying strategic positions in their careers, the easiness of alumni for getting a job, a large number of individuals in surroundings who are working as a data analysts and representative library. The findings also reveals that all the selected indicators are significant so that no indicators need to be excluded. Evaluation of the model shows that the specified model fits the analyzed data. This is indicated by the Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA), and Standardized Root Mean Square Residual (SRMR) values ​​which reach good fit criteria.